ATRIBUT-ATRIBUT YANG MEMENGARUHI SIKAP DAN PREFERENSI KONSUMEN DALAM MEMBELI BUAH APEL DI KOTA SURABAYA DAN KOTA MALANG, PROVINSI JAWA TIMUR - Widiyanto, Nerisa Agnesia; Adhi, Andriyono Kilat; Daryanto, Heny K (Jurnal Ilmu Keluarga dan Konsumen, 2016)
Apple’s consumer will have to make some consideration in purchasing apples because of the appearance of Imported apples in the domestic market. The escalation of apple’s demand and the new policy regarding importing provision and horticultural products development, make it important to study the consumer behavior towards apples. This study was conducted in Surabaya and Malang, and it was chosen purposively. The study involved 200 respondent from two selected city. The data collected were analyzed with descriptive analysis, Fishbein models, and conjoint analysis. The result showed that consumer had positive attitude towards the flesh texture of the local apples. On the other hand, the result showed that consumer had positive attitude towards the prices, taste, size, color, skin condition, and promotion of the import apples. Consumer had preferences for apples with sour taste, medium size, yellowish green color, crispy texture, clean skin, and with price range from Rp26.001,0-Rp34.000,0/kg. The price was the attribute that most preferred by a consumer when making a purchase decision for fruit.